Nature-based solutions for human and environmental resilience: the case of Dolo Ado and Bokolmayo districts, Somali Regional State, Ethiopia - Mekuria, Wolde; Moges, A.; Girma, R.; Yakob, G.; Teshale, T.; Haile, Alemseged Tamiru; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The Somali Region of Ethiopia is prone to climate-induced displacement and hosts the highest number of internally displaced people (IDPs) due to drought nationwide. Addressing the vulnerability of local communities (i.e., refugees, IDPs, and host communities in this study) to natural hazards, such as drought and floods as well as environmental (soil, vegetation) degradation, requires humanitarian and development strategies to reconcile life-saving objectives and environmental safeguarding. With this consideration, implementing nature-based solutions (NbS) could be one option to balance the objectives of life-saving and environmental management activities.